PRAKTIK KAWIN SUNTIK HEWAN (SAPI) DITINJAU DARI HUKUM ISLAM BAIK DALAM PRAKTIK MAUPUN DALAM AKADNYA - Fify Nurul Pertiwi; Lilis Nurani (Academica : Journal of Multidisciplinary Studies, 2020)
This study discusses the Islamic Law Review of the Practice of Injecting Animal (Cows) Mating in Sembukan Village, Sidoharjo District, Wonogiri Regency. Along with the times marked by technological developments, the world of animal husbandry has also experienced developments such as injection marriage and how is the Islamic law review of the practice of injection marriage? From the above problems it is very interesting to study regarding the sale and purchase of male sperm in the case of injection mating. This research on Animal Injecting Mating will be reviewed using three theories, namely the theory of Islamic law, the theory of animal injection practice and the theory of various kinds of contracts in animal injection practice transactions. Regarding the Islamic Law Theory that will be used, namely the Basics of Islamic Law, Types of Islamic Law, Principles and Objectives of Islamic Law, and the Istimbat Method. While the Practice Theory that will be used is the Goals and Strengths or Weaknesses of Injecting Marriage Practices. Then the various kinds of contracts in the animal injection practice transaction that will be used are leasing (wage-wage) and buying and selling.Keywords: Animal Injection Mating; Practice; Akad; Islamic Law.